Evaluating Smoking Cessation Counseling Bundle Behavioral Intervention for Mongolian Adults Who Use Nicotine Patches (Central Asian Journal of Medical Sciences, 2023)
Objectives: The objective of this study is to evaluate the effectiveness of a behavioral intervention based on the World Health Organization (WHO) 5A and 5R guidelines in Mongolia who use the Nicotine Replacement Therapy (NRT) patch. The study aims to assess the impact of the intervention on smoking cessation rate. The finding of this study will contribute to the existing literature on smoking cessation interventions and provide valuable insights into the effectiveness of a behavioral approach in a Mongolian population. Methods: In the intervention study, out of total of 806 people interested in the part of this study. The study team excluded their eligibility criteria of the study participant. A sample of 625 people who fulfilled study inclusion criteria received advice about the negative consequences of tobacco. After that, 479 people decided to quit smoking and 41 people were excluded due to health contraindications, and the final sample 454 people began nicotine replacement therapy to quit smoking. Participants in the treatment group received nicotine replacement patches for 28 days, while those in the counseling group received four sessions of behavioral change counseling (5A, 5R). Results: 454 were found to be eligible to take part in the study and were subsequently assigned to one of two groups, with 230 and 224 participants assigned to each group, respectively. In the second month of follow-up, 90 (39.1%) of participants who received NRT patches quit smoking. The group that received NRT + Behavioral intervention was 1.02 times as successful, or 0.7% more effective, than the group that did not receive behavioral intervention (P=0.872). Conclusion: WHO 5A, 5R brief counselling were more effective than group without behavioral intervention for smoking cessation, but difference was insignificant.